(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
The initial times of work on RBPEC were times of much learning and with that spirit we start our dialogue with our readers. It was, between crises, difficulties, setbacks, challenges and lots of learnings, that we close 2022 and, full of hope, initiate a new year. In 2023, beyond renewed hopes, we wish everyone to have the necessary disposition to rebuild the spaces of Education, Science, Science Education and the Scientific Disclosure. Yes, there’s only the possibility to make a year really new if we have a lot of hope and will to do more, better and different. We believe that in this way, and only in this way, we will make and have a happy new year.